2017
DOI: 10.1161/strokeaha.117.017387
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA H19 Promotes Neuroinflammation in Ischemic Stroke by Driving Histone Deacetylase 1–Dependent M1 Microglial Polarization

Abstract: Background and Purpose-Long noncoding RNA H19 is repressed after birth, but can be induced by hypoxia. We aim to investigate the impact on and underlying mechanism of H19 induction after ischemic stroke. Methods-Circulating H19 levels in stroke patients and mice subjected to middle cerebral artery occlusion were assessed using real-time polymerase chain reaction. H19 siRNA and histone deacetylase 1 (HDAC1) plasmid were used to knock down H19 and overexpress HDAC1, respectively. Microglial polarization and isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
167
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 215 publications
(185 citation statements)
references
References 27 publications
3
167
0
Order By: Relevance
“…According to the previous studies, several lncRNAs act as enhancers of inflammatory responses in AIS by activating inflammation‐related pathways such as NF‐κB pathway, TRL pathway, and JAK/STAT pathway . For instance, increased lncRNA H19 expression is associated with impaired neurological function and increased TNF‐α level in AIS animal models . Antisense non‐coding RNA in the cyclin‐dependent kinase inhibitor 4 locus (ANRIL), an antisense lncRNA co‐clustered with p15/CDKN2B‐p16/CDKN2A‐p14/ARF, is overexpressed in cerebral infarction rat models and plays a pro‐inflammatory role by activating NF‐κB pathway .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previous studies, several lncRNAs act as enhancers of inflammatory responses in AIS by activating inflammation‐related pathways such as NF‐κB pathway, TRL pathway, and JAK/STAT pathway . For instance, increased lncRNA H19 expression is associated with impaired neurological function and increased TNF‐α level in AIS animal models . Antisense non‐coding RNA in the cyclin‐dependent kinase inhibitor 4 locus (ANRIL), an antisense lncRNA co‐clustered with p15/CDKN2B‐p16/CDKN2A‐p14/ARF, is overexpressed in cerebral infarction rat models and plays a pro‐inflammatory role by activating NF‐κB pathway .…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] For instance, increased lncRNA H19 expression is associated with impaired neurological function and increased TNF-α level in AIS animal models. 23 Antisense non-coding RNA in the cyclin-dependent kinase inhibitor 4 locus (ANRIL), an antisense lncRNA co-clustered with p15/CDKN2B-p16/CDKN2A-p14/ ARF, is overexpressed in cerebral infarction rat models and plays a pro-inflammatory role by activating NF-κB pathway. 24 Likewise, ln-cRNA Gm4419 could activate NF-κB pathway and contributes to cell damage in oxygen-glucose-deprived cerebral microglial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have demonstrated that RMST silencing protected neurons against OGD‐induced apoptosis in vitro, decreased cerebral infarction size and neuronal apoptosis and improved neurological function in MCAO mice . Accumulating evidence demonstrated that lncRNAs participate in the progression of neurological disorders through regulating microglial polarization, including H19, tumor suppressor candidate 7 (TUSC7), small nucleolar RNA host gene 1 (SNHG1) . However, to date, the association between ischemic stroke‐induced microglial activation and RMST upregulation has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,16,17 Although the function of HOTTIP has been widely studied in several tumors, its role in ischemic stroke remains elusive. 13,14,16,17 Although the function of HOTTIP has been widely studied in several tumors, its role in ischemic stroke remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…During ischemic attacks and acute glucose deprivation, glycolytic metabolism in the brain is impaired, leading to neuron death. 17 HOXA transcript at the distal tip (HOTTIP) is a newly identified lncRNA located at the 5′ end of the HOXA gene cluster. 13,14 Recently, studies have discovered that a series of lncRNAs are abnormally expressed and play vital roles in ischemic stroke.…”
mentioning
confidence: 99%